If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -4 = 6x + 11 Combine like terms: 7 + -4 = 3 3 = 6x + 11 Reorder the terms: 3 = 11 + 6x Solving 3 = 11 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + -6x = 11 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -6x = 11 + 0 3 + -6x = 11 Add '-3' to each side of the equation. 3 + -3 + -6x = 11 + -3 Combine like terms: 3 + -3 = 0 0 + -6x = 11 + -3 -6x = 11 + -3 Combine like terms: 11 + -3 = 8 -6x = 8 Divide each side by '-6'. x = -1.333333333 Simplifying x = -1.333333333
| 8+4x=5x+5 | | -3y-19+5y=-22 | | 4x-6x-16=-2x+3-16 | | 7x+2=5x+15 | | .25x-8+.5x=19 | | 10-2x=3(x+4)-2 | | 10h=-.1 | | 9=2j+1 | | 9=1+2b | | 3x+2(x+2)=5x+4 | | -2.5s=25 | | 2x+2+7x=-6x-2x | | .4x-8+.5x=19 | | 2(x+1)=3(x+4) | | 4+2i=4 | | 12y=1x+b | | -8g=.48 | | 0.6r=.0005 | | -7y=-6.3 | | 2(x+1)=3(x+4)+10 | | 0.6=r+.0005 | | (3x^2-2x^2+2x-5)*x+1= | | x+(-28)=53 | | .3k=-12 | | 14=6-4y | | 3(10x+4)=8(3x+6) | | z^2=z-12 | | 5r=-.15 | | 3x+2(x+2)=5-4x+2 | | (2x-5)/6-(3x-2)/3=(2x-5)/2 | | .0005=0.6r | | 3x+14=7x+2 |